Chemical and rheological characteristics of rejuvenated bitumen with typical rejuvenators. (1st March 2021) - Huang, Wentong; Guo, Yunfei; Zheng, Yu; Ding, Qile; Sun, Can; Yu, Jiangmiao; Zhu, Minye; Yu, Huayang
Highlights: The selected rejuvenators make the aged bitumen softer. FTIR and GPC are reliable tests for rejuvenating effect. Sulfoxide index, Mw, PD, and LMS correlate well with rheological parameters. Abstract: In recent years, reclaimed asphalt pavement (RAP) is widely used in pavement construction because of its merits on both economic and environmental aspects. The use of RAP contributes to significant reduction on resource consumption, construction emission and the overall construction costs. To better utilize RAP, different rejuvenators are applied to soften the aged bitumen and enhance the blending efficiency between new and aged bitumen. Although the engineering performance of RAP mixtures has been well studied, the interaction among new bitumen, aged bitumen and rejuvenators still remains unclear. This study is conducted for rejuvenating mechanism investigation by chemical and rheological analyses. To achieve this goal, three typical rejuvenators (soft bitumen, warm mix surfactant, and bio-rejuvenator) were mixed with aged bitumen. Various tests including Dynamic Shear Rheometers (DSR), Fourier Transform Infrared (FTIR) spectroscopy and Gel Permeation Chromatography (GPC) were performed. It is found that all three rejuvenators exhibited certain effect on restoring rheological performance of aged bitumen. The softening effect of DAT and bio-rejuvenator were strongest when aged bitumen percentages were 30% and 80% respectively. The incorporation of appropriate percentage of aged bitumen improved the fatigue lives of rejuvenated bitumen. Soft bitumen exhibited the optimal performance on improving fatigue resistance of rejuvenated bitumen. Additionally, the alterations of functional group indices and molecular distribution can be considered as explanations for the regenerating effect of rejuvenators. Moreover, the sulfoxide index of FTIR and three GPC parameters can be used as reliable indicators to predict the rheological properties of rejuvenated bitumen.